Nanoparticle-encapsulated camptothecin: epigenetic modulation in DNA repair mechanisms in colon cancer cells - Farhana, Aisha; Ee, Avin Hwan Koh; Jia, Bei Tong; Alsrhani, Abdullah; Subbiah, Suresh Kumar; Pooi, Ling Mok (MDPI, 2021)
Molecular crosstalk between the cellular epigenome and genome converge as a synergistic driver of oncogenic transformations. Besides other pathways, epigenetic regulatory circuits exert their effect towards cancer progression through the induction of DNA repair deficiencies. We explored this mechanism using a camptothecin encapsulated in β-cyclodextrin–EDTA–Fe3O4 nanoparticles (CPT-CEF)-treated HT29 cells model. We previously demonstrated that CPT-CEF treatment of HT29 cells effectively induces apoptosis and cell cycle arrest, stalling cancer progression. A comparative transcriptome analysis of CPT-CEF-treated versus untreated HT29 cells indicated that genes controlling mismatch repair, base excision repair, and homologues recombination were downregulated in these cancer cells. Our study demonstrated that treatment with CPT-CEF alleviated this repression. We observed that CPT-CEF exerts its effect by possibly affecting the DNA repair mechanism through epigenetic modulation involving genes of HMGB1, APEX1, and POLE3. Hence, we propose that CPT-CEF could be a DNA repair modulator that harnesses the cell’s epigenomic plasticity to amend DNA repair deficiencies in cancer cells.